Development of Chemical Equilibrium E-Learning Content Based on Guided Discovery Blended Learning for Senior High School - Fitrah Mey Harmi Siregar; Jumasari Siregar; Amalia Putri Lubis (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
The Covid-19 pandemic suddenly hit Indonesia so the situation was out of control, including in the world of education. The government through the Ministry of Education and Culture, the education office, educators and education staff, students, and the public are confused because they must carry out distance learning online, offline, and a combination. In this study, the development of E-learning on chemical equilibrium material based on guided discovery learning was carried out using the Plomp development model. Three high school chemistry teachers validated E-learning. The practicality test carried out in class XI SMAN Mapat Tunggul Selatan. This study aims to help the learning process in the era of the covid-19 pandemic. Content and construct validation obtained scores of 0.86 and 0.88. Based on the practicality test, this e-learning was declared valid and feasible with the support of Aiken’s test of 0.83. The result of e-learning can be used in teaching and learning activities. E-learning can also be accessed easily anytime, anywhere, and with anyone with full use of internet access.